2018
DOI: 10.1111/epi.14599
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends and patterns in carbamazepine use, related severe cutaneous adverse reactions, and HLA‐B*15:02 screening: A nationwide study

Abstract: Objective: After discovering the association between the HLA-B*15:02 allele and carbamazepine-related severe cutaneous adverse reactions (SCARs), particularly in Southeastern Asian populations, clinical strategies to prevent carbamazepine-related SCARs have changed. We aimed to investigate 10-year trends in carbamazepine use and carbamazepine-related SCARs and to examine the patterns and determinants of HLA-B*15:02 screening in Taiwan. Methods: A nationwide study was performed using Taiwan's National Health In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The implementation of these safety measures corresponds with a significant decline from 2011 in the number of CBZ‐associated drug‐injury relief applications ( Figure ). Another analysis of the National Health Insurance found that CBZ prescriptions fell steadily from 2005−2014, whereas HLA‐B*15:02 genetic testing rose significantly from 2010−2014; at the same time, cases of CBZ‐induced SCARs declined significantly from 2011 . From this real‐world evidence, it can be seen that in the case of CBZ, the introduction of several administrative measures and the active promotional initiatives of the TDRF combined to deliver tangible reductions in drug injury, and indicates that the drug‐injury relief system in Taiwan not only offers postinjury relief but is also playing a substantial role in pharmacovigilance and drug safety.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of these safety measures corresponds with a significant decline from 2011 in the number of CBZ‐associated drug‐injury relief applications ( Figure ). Another analysis of the National Health Insurance found that CBZ prescriptions fell steadily from 2005−2014, whereas HLA‐B*15:02 genetic testing rose significantly from 2010−2014; at the same time, cases of CBZ‐induced SCARs declined significantly from 2011 . From this real‐world evidence, it can be seen that in the case of CBZ, the introduction of several administrative measures and the active promotional initiatives of the TDRF combined to deliver tangible reductions in drug injury, and indicates that the drug‐injury relief system in Taiwan not only offers postinjury relief but is also playing a substantial role in pharmacovigilance and drug safety.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the predisposition, together with identification in a cohort study that prospective genotyping reduced the incidence of SJS/TEN, has led to the recommendation in drug labels that HLA‐B*15:02 screening should be undertaken prior to the use of CBZ in South‐East Asian populations. In Taiwan, after screening was introduced, cases of CBZ‐induced SJS/TEN have declined by 87% over a 10‐year period, but this is not all due to the use of HLA‐B*15:02 testing because the use of CBZ also decreased by 83% over the same time period . Indeed only 25% of new users were screened before given CBZ, highlighting that implementation is far from perfect.…”
Section: Hla and Drug Hypersensitivitymentioning
confidence: 99%
“…In Taiwan, after screening was introduced, cases of CBZ-induced SJS/TEN have declined by 87% over a 10-year period, but this is not all due to the use of HLA-B*15:02 testing because the use of CBZ also decreased by 83% over the same time period. 4 Indeed only 25% of new users were screened before given CBZ, highlighting that implementation is far from perfect. This is also reflected in a study from Hong Kong where the availability of a genetic test for HLA-B*15:02 drove clinicians away from the use of CBZ to other drugs, which were also associated with SJS/TEN, such that the total incidence of anticonvulsant-induced SJS/ TEN remained stable despite a decrease in CBZ-induced SJS/TEN.…”
Section: Hla and Drug Hypersensitivitymentioning
confidence: 99%
“…Phenytoin SJS/TEN has been strongly linked to the HLA‐B*15:02 allele and less commonly to other human leucocyte antigen (HLA)‐B alleles of the same B75 serotype ( HLA‐B*15:21 , B*15:11 , B*15:08 ) originally reported in Han Chinese from Taiwan but subsequently confirmed in other Asian countries including Malaysia, China, Thailand and India, where its frequency can be >10% . In Taiwan where screening for HLA‐B*15:02 is reimbursed, the use of carbamazepine and cases of carbamazepine‐related SCAR have declined . In Korean, Japanese and European populations, phenytoin‐associated DRESS due to HLA‐B*15:02 is rare due to very low allele frequency (< 0.5%).…”
Section: Introductionmentioning
confidence: 99%
“…1 In Taiwan where screening for HLA-B*15:02 is reimbursed, the use of carbamazepine and cases of carbamazepine-related SCAR have declined. 3 In Korean, Japanese and European populations, phenytoin-associated DRESS due to HLA-B*15:02 is rare due to very low allele frequency (< 0.5%). In a Malay population, 4 a different HLA-B allele in the B75 serotype, HLA-B*15:13 was associated with phenytoin SJS/TEN and DRESS.…”
Section: Introductionmentioning
confidence: 99%